SECURING NATIONAL AND REGIONAL ENERGY: INDONESIA'S POLICY IN THE TRANS-ASEAN GAS PIPELINE PROJECT - Aspin Nur Arifin Rivai; Riska Luneto (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
The regional cooperation policy for the development of the Trans-ASEAN Gas Pipeline (TAGP) megaproject is one of Indonesia's efforts to secure national energy sources. The purpose of this study is to analyze the effectiveness of the policies that have been implemented by the Indonesian Government in responding to various problems of energy insecurity in the gas sector. Indonesia's policy to actively participate in the TAGP project is believed to be one of the solutions to overcoming the national and regional gas energy crisis, besides, energy security caused many various other security issues. This article uses a non-traditional security perspective to see why and how energy security become a huge issue today. The result that we found, in this case, is that the effectiveness of the policy cannot be assessed optimally, for example, the guaranteed stability of natural gas energy security at the national level and regional, both in terms of availability, distribution, and affordability that still needs continuous improvement.